Alguns parâmetros utilizados na avaliação hidrogeoquímica de um campo petrolífero na Bacia de Campos (RJ): estudos preliminares - Azevedo, Sergio Luiz Nogueira de; Rodrigues, Carla Valéria Martins; Castro, Antonio Carlos Jacome de (Anuário do Instituto de Geociências, 1994)
The study of the formation water is receiving a great importance, as a tool in the studies of migration, weathering and accumulation of hidrocarbons. The present study is based on the interpretation of chemical and isotopic data of formation water belonging to Lagoa Feia and the Macae Formations of the Campos Basin oil field. The purpose of mecanisms for evolution and genetic classification of formation water, that was intended in the recent study, determined theirs sources and hydrogeological environments in question. Finnaly, these basic facts were related with the possibility, or not, of accumulation of hydrocarbons. The sample from Campo X point towards existence of "stagnated environments" with low circulation of water, inclined for accumulation of hydrocarbons, shuting out sample 4 (four), belong to Lagoa Feia Formation, is described how indued in the hydrodinamic circulation zone. The strong point of dolomitization and water reaction with clay minerals shows an influence of the meteoric diagenetic environments, proving that before the establishment of estagnated condition observed, probably the water of Campo X received a strong meteoric influence. The waters studied are resulted of one mixture of waters from different brines among these waters originated by evaporation are included. It's possible, because high brines of Lagoa Feia Formation could have some vulcanic contribution.